Perencanaan Struktur Beton Bertulang Tahan Gempa Berlantai 4 (Studi Kasus Gedung Baru Kampus I Universitas Teknologi Yogyakarta) - Algazt Arsyad Masagala; Faqih Ma'arif (Universitas Muhammadiyah Yogyakarta, 2016)
The new building in campus one of Universitas Teknologi Yogyakarta which consists of four floors is analyzed by using Intermediate Moment Resisting Frame (IMRF) to be able to withstand gravity and seismic load. The planning of reinforced concrete structure in this building is aimed to 1) to calculate the gravity and seismic plan load that works for the new building in campus one of Universitas Teknologi Yogyakarta, 2) to find the dimension of beam and column that able to withstand the working seismic plan load, 3) to determine the formation of beam and column reinforcement from the analysis result by using Intermediate Moment Resisting Frame (IMRF). The building structure analysis is conducted using SAP 2000 V.11 program. The planning of reinforced concrete structure is assumed as Intermediate Moment Resisting Frame/Structure (IMRF). The planning of beam and column is conducted by using the dimension in the field. The reinforced planning is conducted base on the Assessment Regulation of Reinforced Concrete Structure for Infrastructure with SNI 03-2847-2002. The assessment of static equivalent seismic load is referred to Standards of Earthquake Resistance Planning for Buildings with SNI-03-1727-2002. Based on the analysis by using Intermediate Moment Resisting Frame (IMRF), the planning of reinforced concrete structure including dimension and reinforced formation of beam and column has fulfilled the requirements and save based on field assessment.